Infiltrating Cardiac Synovial Sarcoma Presenting as Acute Cerebrovascular Accident - Kelechukwu U. Okoro; Matthew D. Roby; David C. Sane; Robert E. Budin (Case Reports in Medicine)
Primary cardiac sarcoma is a rare malignant myocardial neoplasm that does not exhibit gender predominance or age predilection. The classification of these tumors includes several subtypes, of which synovial sarcoma is a rare manifestation. When present, these tumors portend a poor prognosis with high morbidity and mortality that is attributable to their inherent infiltrative capacity, especially in the absence of treatment. The general consensus for treatment is surgical excision and neoadjuvant chemotherapy and radiotherapy. In this report, a case of synovial sarcoma involving the left ventricular outflow tract and aortic valve is presented.